Dmitruk Stepan Yevgeniyevich — organizer, teacher, scientist - Article Editorial (Бюллетень сибирской медицины, 2011)
The creative biography of Professor S.Ye. Dmitruk, prominent Russian pharmacologist and scientist, doctor of pharmaceutical sciences, is presented. For more than 30 years he headed the Pharmaceutical Faculty of the Tomsk Medical Institute - Siberian State Medical University.